2014
DOI: 10.1586/17512433.2015.974555
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to oncologic drugs: spontaneous reporting and signal detection

Abstract: Oncology is one of the areas of medicine with the most active research being conducted on new drugs. New pharmacological entities frequently enter the clinical arena, and therefore, the safety profile of anticancer products deserves continuous monitoring. However, only very severe and (unusual) suspected adverse drug reactions (ADRs) are usually reported, since cancer patients develop ADRs very frequently and some practical selectivity must be used. Notably, a recent study was able to identify 76 serious ADRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Our in vivo study also suggested Asp-UA possessed higher anti-metastasis efficacy with lower toxicity in comparison with UA or Asp alone. Oncologic therapeutic agent of high-efficiency and low-toxicity is an area of unmet clinical need [51]. The present study indicated that Asp-UA was effective in prevention and treatment of breast cancer metastasis, especially low toxic to the hosts, which could manifest a high clinical value.…”
Section: Discussionmentioning
confidence: 62%
“…Our in vivo study also suggested Asp-UA possessed higher anti-metastasis efficacy with lower toxicity in comparison with UA or Asp alone. Oncologic therapeutic agent of high-efficiency and low-toxicity is an area of unmet clinical need [51]. The present study indicated that Asp-UA was effective in prevention and treatment of breast cancer metastasis, especially low toxic to the hosts, which could manifest a high clinical value.…”
Section: Discussionmentioning
confidence: 62%
“…A shift in the trend of reporting ADRs by health professionals and patients is considered to be an important element to improve patient’s safety and adherence to targeted therapies. The involvement of patients in Pharmacovigilance reporting systems (PVRS) is a potential strategy to increase the knowledge of oncological ADRs, increase patient’s satisfaction, and reduce the phenomenon of under-reporting [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacovigilance is today structured in complex communication systems, registries and databases. It is the fundamental approach for the early detection of new signals of risk for patients taking drugs [ 2 ]. Pharmacovigilance involves the detection and spontaneous reporting of adverse drug reactions (ADRs) occurring during drug therapy.…”
Section: Introductionmentioning
confidence: 99%